2022
DOI: 10.3389/fimmu.2022.866925
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intoxication With Alcohol Reduces Trauma-Induced Proinflammatory Response and Barrier Breakdown in the Lung via the Wnt/β-Catenin Signaling Pathway

Abstract: BackgroundTrauma is the third leading cause of mortality worldwide. Upon admission, up to 50% of traumatized patients are acutely intoxicated with alcohol, which might lead to aberrant immune responses. An excessive and uncontrolled inflammatory response to injury is associated with damage to trauma-distant organs. We hypothesize that, along with inflammation-induced apoptosis, the activation of the Wnt/β-catenin signaling pathway would cause breakdown of the lung barrier and the development of lung injury aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…In a recent study applying this model, it was shown that aged mice had significantly lower total bone and callus volume, decreased share of callus per total bone volume, less trabecular structures as well as the reduction of the elastic limit (31), thus, our model of femoral fracture mimics the human situation. Furthermore, it was demonstrated that THFx induced an uncontrolled inflammatory response and lung barrier breakdown in young mice (33), findings that support our hypothesis. This study's results have the potential to guide future research and pre-clinical approaches for addressing these conditions in both younger and older populations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a recent study applying this model, it was shown that aged mice had significantly lower total bone and callus volume, decreased share of callus per total bone volume, less trabecular structures as well as the reduction of the elastic limit (31), thus, our model of femoral fracture mimics the human situation. Furthermore, it was demonstrated that THFx induced an uncontrolled inflammatory response and lung barrier breakdown in young mice (33), findings that support our hypothesis. This study's results have the potential to guide future research and pre-clinical approaches for addressing these conditions in both younger and older populations.…”
Section: Discussionsupporting
confidence: 86%
“…Trauma is the leading cause of death and disability worldwide ( 35 ). In young mice, femoral fracture following pressure-controlled hemorrhagic shock can cause increased uncontrolled inflammation in the lungs as well as disruption of the pulmonary barrier ( 33 ), yet the current research has not fully explained the effects of aging on lung injury and the pulmonary inflammatory response after THFx. Our study aimed to investigate how aging influences the typical NF-κB signaling pathway as well as the expression of inflammasome components that mediate the lung inflammatory response after THFx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cytoplasm, axis inhibitor (AXIN), glycogen synthase kinase 3β (GSK-3β), and adenomatous polyposis coli (APC) jointly promote β-catenin ubiquitination and degradation, thereby inhibiting signaling [10]. The Wnt/β-catenin pathway is critical in lung development and repair [7,11,12], and its abnormal regulation is closely correlated with lung diseases progression, such as lung cancer, bronchopulmonary dysplasia, idiopathic pulmonary fibrosis (IPF), asthma, and acute respiratory distress syndrome (ARDS) [10,[13][14][15][16]. Its roles include regulating inflammation, oxidative stress, cell differentiation, and apoptosis [12,17,18].…”
Section: Introductionmentioning
confidence: 99%